Selección de color dentario utilizando espectrofotometría y método visual. Revisión Bibliográfica. - Avendaño Arenas, Alejandro; Astorga Gallardo, Carlos; Cabezas Osorio, Verónica (Journal of Oral Research, 2021)
The demand for esthetic dentistry in clinical practice has been steadily increasing. When a dental piece is rehabilitated, it is very important to restore both the morpho-functional characteristics as well as the aesthetic appearance.